Semiautomated computer analysis of vessel growth in preterm infants without and with ROP. Issue 12 (5th December 2003) - Swanson, C; Cocker, K D; Parker, K H; Moseley, M J; Fielder, A R
Abstract : Aims: To measure characteristics of the retinal blood vessels close to the optic disc in full term and preterm infants, with and without retinopathy of prematurity (ROP), using digital imaging. To determine whether these measures are indicative of the presence or severity of ROP in the retinal periphery. Methods: 52 digital fundus images from 42 babies were analysed with a semiautomated analysis program developed at Imperial College London. Analysis was limited to the principal temporal vessels close to the optic disc: recording venular diameter and arteriolar diameter and tortuosity. Results: Each result was categorised by the gestational age of the infant ("very premature" 24–27 weeks, "moderately premature" 28–31 weeks, and "near term" ⩾32 weeks) and by the highest stage of ROP present ("no ROP, " "mild ROP" stage 1 or 2, and "severe ROP" stage 3). Arteriolar tortuosity was found to vary significantly (Kruskal-Wallis p = 0.002) with ROP severity. Although venular and arteriolar diameters increased monotonically with ROP severity the differences were not significant. Venular diameter, arteriolar diameter, and arterial tortuosity did not vary significantly between gestational age groups. Conclusions: This study confirms it is possible to quantify the size and tortuosity of retinal blood vessels in term and preterm babies using digital image analysis software. This method detected significant increases in arteriolar tortuosity with increasing ROP severity.